2019
DOI: 10.1038/s41467-019-08873-z
|View full text |Cite
|
Sign up to set email alerts
|

Gamma oscillations in somatosensory cortex recruit prefrontal and descending serotonergic pathways in aversion and nociception

Abstract: In humans, gamma-band oscillations in the primary somatosensory cortex (S1) correlate with subjective pain perception. However, functional contributions to pain and the nature of underlying circuits are unclear. Here we report that gamma oscillations, but not other rhythms, are specifically strengthened independently of any motor component in the S1 cortex of mice during nociception. Moreover, mice with inflammatory pain show elevated resting gamma and alpha activity and increased gamma power in response to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
112
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 66 publications
15
112
0
2
Order By: Relevance
“…Second, tACS might be able to modulate neural oscillations but neural oscillations might not be causally involved in the processing of pain. This seems unlikely since optogenetic and invasive electrical modulations of neural oscillations in somatosensory and prefrontal brain areas effectively modulate acute and chronic pain in animals [43,51]. Third, tACS might in principle be able to modulate neural oscillations and pain but the tACS parameters used in the present study were not optimal.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Second, tACS might be able to modulate neural oscillations but neural oscillations might not be causally involved in the processing of pain. This seems unlikely since optogenetic and invasive electrical modulations of neural oscillations in somatosensory and prefrontal brain areas effectively modulate acute and chronic pain in animals [43,51]. Third, tACS might in principle be able to modulate neural oscillations and pain but the tACS parameters used in the present study were not optimal.…”
Section: Discussionmentioning
confidence: 89%
“…[11,24,27,30,39,50]). Moreover, animal studies relying on optogenetics and invasive electrical stimulation have indicated that these changes of neural oscillations are causally involved in generating pain [43,51]. Thus, modulating neural oscillations to eventually modulate pain is a promising novel approach for the treatment of pain [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, a preclinical study has shown that activity in the primary somatosensory cortex is able to enhance pain by recruitment of the 5HT3 receptor facilitatory system that we have discussed previously (Tan et al 2019). A key patient study in OA used imaging and psychophysics (Soni et al 2019) and consolidated many of the issues that we have covered in this review.…”
Section: Brain Areas That Control Descending Inhibitory Pathwaysmentioning
confidence: 88%
“…The role of neurophysiology in these processes has revealed a similarly overlapping feature of pain and cognition-cortical gamma oscillations. High-frequency gamma activity has long been associated with cognition and attention [8,9] but has also been shown to encode ongoing pain [10,11]. Moreover, surgically implanted devices such as spinal cord stimulation have shown the potential to modulate cortical gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) activity [12], supporting the hypothesis of supraspinal mechanisms of action for spinal, and potentially peripheral, neuromodulation.…”
Section: Introductionmentioning
confidence: 93%